2011
DOI: 10.1177/0192623311399788
|View full text |Cite
|
Sign up to set email alerts
|

PTHrP Treatment Fails to Rescue Bone Defects Caused by Hedgehog Pathway Inhibition in Young Mice

Abstract: The advent of molecular targeted therapies offers the hope of therapeutic advance in the fight against cancer. However, this hope is tempered by recent findings that certain targeted therapies may have unique side effects. The hedgehog (HH) pathway is a potential target for treatment of several cancers, including basal cell carcinoma (BCC) and a subset of medulloblastoma (MB). Recent clinical trials in adults have shown responses to HH pathway inhibition in both BCC and MB. However, concerns have been raised a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…Although we found that treatment with an IHH signaling inhibitor reduced the formation of chondroma-like lesions in Fgfr3 cKO mice, adverse secondary effects were induced, including premature growth plate fusion leading to a shorter long bone, which is similar to what was observed in mice with chondrocyte-specific deletion of IHH [ 61 ]. Other types of SMOi such as HhAntag had similar effects on the skeleton [ 62 ]. Thus, given that cartilaginous tumors occur mostly in children, caution is required when using SMOi to treat young patients with enchondroma and osteochondroma.…”
Section: Discussionmentioning
confidence: 99%
“…Although we found that treatment with an IHH signaling inhibitor reduced the formation of chondroma-like lesions in Fgfr3 cKO mice, adverse secondary effects were induced, including premature growth plate fusion leading to a shorter long bone, which is similar to what was observed in mice with chondrocyte-specific deletion of IHH [ 61 ]. Other types of SMOi such as HhAntag had similar effects on the skeleton [ 62 ]. Thus, given that cartilaginous tumors occur mostly in children, caution is required when using SMOi to treat young patients with enchondroma and osteochondroma.…”
Section: Discussionmentioning
confidence: 99%
“…This was particularly important in the development of SMO inhibitors, as fears of developmental bone toxicities, because of the well-known role of the HH pathway in the bone growth plate [ 9 ], were borne out in the clinic [ 10 , 11 ]. This resulted in a Federal Drug Administration restriction on the use of SMO inhibitors in young children prior to completion of bone growth that, unfortunately, was only put in place after bone malformations, first described in young mice [ 12 , 13 ], were recapitulated in children.…”
Section: Target Identificationmentioning
confidence: 99%
“…Ihh acts with PTHrP in a negative feedback loop to regulate early chondrocyte differentiation and hypertrophic differentiation ( 22 ). Blocking Ihh signaling with cyclopamine has been reported to delay chondrocyte hypertrophy in PTHrP knockout embryos, whereas upregulating Ihh signaling in the postnatal cartilage led to accelerated chondrocyte hypertrophy during secondary ossification, indicating that Ihh signaling promotes chondrocyte hypertrophy independently of PTHrP, which may be mediated by Wnt/β-catenin signaling ( 23 , 24 ). As chondrocytes go through a program of proliferation and subsequent differentiation into hypertrophic chondrocytes, PTHrP maintains chondrocyte proliferation and delays their further differentiation ( 25 ).…”
Section: Discussionmentioning
confidence: 99%